Analisis Tahapan Konflik Pilkada Kabupaten Sumbawa Tahun 2020 - Ahmad Taubih Lalu; Aswar Tahir (Institut Agama Islam Tribakti (IAIT) Kediri, 2023)
This research is to explain the stages of the 2022 Sumbawa Regency Pilkada conflict. The method used is a qualitative method with a case study approach. The data were obtained from the narrative of communication conversations through social media (facebook) which discussed support for the figures of the two Sumbawa regent candidate pairs. The data analysis technique that can be used in analyzing qualitative data is thematic analysis. The results showed that the pre-conflict stage was the initial stage of the conflict stage, this conflict was triggered by the issue of the 2020 Sumbawa Regency Pilkada. The conflict began to open up when the appearance of Novi, the governor's sister as a candidate for Deputy Regent, was claimed as a form of political dynasty, coupled with the issue during the governor's campaign he helped Mo-Novi by providing livestock assistance to voters. Meanwhile, the escalation of the conflict was triggered by a comment by a Mo-Novi supporter who insulted Jarot-Mohlis and his supporters as Dogs because the Jarot-Mohlis pair did not accept their defeat. Meanwhile, as a result of the conflict, there has been no attempt to meet the candidate pairs, supporters have not yet greeted each other because of different choices and the feeling of kinship is increasingly stretched. In post-conflict, there is no attempt at reconciliation process, conflicts are reconciled naturally along with the end of the election period.